Witraże dziecięcego „bycia w życiu” – dobrostan versus obrazy codzienności - Justyna Kusztal; Małgorzata Turczyk (Problemy Wczesnej Edukacji)
The aim of the article is to present the situation of children in Poland in the light of the analysis of documents of public institutions and non-governmental organizations whose domain of activity is the protection of children’s rights. The context of the analyzes undertaken by the authors is an interdisciplinary current of childhood studies, and in particular the discourses devoted to caring for a child. Nowadays, the most visible discourse of child’s well-being requires observing particular areas of children’s participation in social life and asking questions about the actual situation of the child in our country, development opportunities and difficulties in implementing children’s rights and ensuring its well-being. This means attempting to describe a child’s stained glass window „being in life”, actual or only apparent participation in particular areas of child’s activity in recent years.